2001
DOI: 10.1128/jb.183.16.4866-4875.2001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Phenolate Siderophores by the Multicopper Oxidase Encoded by theEscherichia coli yacKGene

Abstract: A gene (yacK) encoding a putative multicopper oxidase (MCO) was cloned from Escherichia coli, and the expressed enzyme was demonstrated to exhibit phenoloxidase and ferroxidase activities. The purified protein contained six copper atoms per polypeptide chain and displayed optical and electron paramagnetic resonance (EPR) spectra consistent with the presence of type 1, type 2, and type 3 copper centers. The strong optical A 610 (⌭ 610 ‫؍‬ 10,890 M ؊1 cm ؊1) and copper stoichiometry were taken as evidence that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
112
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 53 publications
9
112
0
Order By: Relevance
“…In the latter hypothesis, CopC and CopA may function together in copper resistance with CopA oxidizing Cu(I) bound to CopC to the less toxic Cu(II) form, as supported by genetic studies on the two homologues of these proteins from E. coli (47,48). Alternatively, copper delivered by CopC to CopA could catalyze the oxidase activity of CopA, as suggested by the copper-inducible oxidation of siderophores by CueO in E. coli (49).…”
Section: Discussionmentioning
confidence: 98%
“…In the latter hypothesis, CopC and CopA may function together in copper resistance with CopA oxidizing Cu(I) bound to CopC to the less toxic Cu(II) form, as supported by genetic studies on the two homologues of these proteins from E. coli (47,48). Alternatively, copper delivered by CopC to CopA could catalyze the oxidase activity of CopA, as suggested by the copper-inducible oxidation of siderophores by CueO in E. coli (49).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, fungal MCOs (laccases) (Hofer and Schlosser 1999;Schlosser and Hofer 2002) have been described that can oxidize Mn(II) to Mn (III). Some MCOs such as ceruloplasmin show a high degree of substrate specificity and others such as laccase possess a more relaxed substrate specificity oxidizing many different substrates including metals and phenolic compounds (Stoj and Kosman 2003) (Solano et al 2001) (Kim et al 2001). Fe(II) oxidation and fungal Mn(II) oxidation by MCOs serve as models for bacterially mediated Mn(II) oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In general, multicopper oxidases couple four one-electron substrate oxidation steps to the four-electron reduction of dioxygen to water (14). CueO can oxidize a range of substrates in vitro, including catechols, siderophores, and Fe(II) (10), and this activity is greatly enhanced in the presence of excess (ϳ100 M) copper(II) ions (10,15), suggesting that binding of a labile copper is important for enzymatic activity. We recently determined the crystal structure of CueO at 1.4-Å resolution (15) and showed that its structure is similar to that of other multicopper oxidases, such as ascorbate oxidase (16) and several laccases (17)(18)(19).…”
mentioning
confidence: 99%